Adaptive Load Frequency Control for Interconnected Grids Using Ant Lion Optimization - Kar, Manoj Kumar; Sharma, Chetan; Sabat, Jogeswara; Mohanty, Jnanaranjan; Raman, Jeygopi (Engineering, Technology & Applied Science Research, 2026)
This paper presents an Ant Lion Optimization (ALO) algorithm for Load Frequency Control (LFC) of a three-area interconnected power system, which utilizes a Proportional–Integral–Derivative (PID) controller. The LFC problem is essential for maintaining system stability and dependability by balancing power generation and load demand. The study determines the optimal PID controller settings to reduce frequency oscillations and improve dynamic performance using sophisticated metaheuristic optimization techniques, such as the ALO algorithm. MATLAB/Simulink simulations are used to assess the controller’s performance and implementation. The simulation is run under a step load disturbance to demonstrate the efficacy of the suggested model. The robustness of the suggested scenario is confirmed by the fact that the control target can still be accomplished even when governor and turbine parameters alter. The Integral of Time-weighted Absolute Error (ITAE) is used to compare the simulation results obtained by different optimization strategies. The study demonstrates that ALO significantly improves the dynamic performance of LFC in interconnected power systems. It achieves faster settling time, reduced frequency deviations, and enhanced system stability compared to traditional methods. ALO-based controllers also show robust adaptability to load variations and parameter uncertainties.